Simple bacterial preservation medium and its application to proficiency testing in water bacteriology. - Brodsky, M H (1978)
A medium composed of nutrient broth, 1.8% boric acid, and 1% sodium chloride at pH 7.0 was shown to maintain the stability of Escherichia coli cultures for up to 10 days at room temperature. By using this preservation medium for preparing a simulated sample a successful proficiency test survey in water bacteriology was conducted.